On subgenera of the genus Prionyx Vander Linden, 1827 (Hymenoptera: Sphecidae), with establishment of a new subgenus - Danilov, Yuriy N.; Odintsev, Oleg A. (Zootaxa, 2023)
Because of its highly external morphological diversity, the genus Prionyx Vander Linden, 1827 has been divided into different species-groups or subgenera. The use of these species-groups or subgenra has just been disordered by several authors. Therefore, based on specimens of most worldwide Prionyx species, we here studied and proposed recognition of six subgenera of Prionyx, namely Calosphex, Harpactopus, Neosphex, Foxiprionyx, Prionyx, and Priononyx. Of these subgenera, Foxiprionyx subgen. nov., based on Prionyx foxi Bohart et Menke, 1963, is established as a new subgenus. Whereas Foxiprionyx, Neosphex, and Priononyx are distributed in the New World, Calosphex, Harpactopus and Prionyx are distributed in the Old World. The key to subgenera of Prionyx is provided.